2017
DOI: 10.14254/2071-789x.2017/10-3/8
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency vs Effectiveness: a Benchmarking Study on European Healthcare Systems

Abstract: ABSTRACT. This paper illustrates a benchmarking study concerning the healthcare systems in 32 European countries as of 2011 and 2014. Particularly, this study proposes a two-dimensional approach (efficiency/effectiveness models) to evaluate the performance of national healthcare systems. Data Envelopment Analysis has been adopted to compute two performance indices, measuring efficiency and effectiveness of these healthcare systems. The results of the study emphasize that the national healthcare systems achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 39 publications
(36 reference statements)
1
34
0
Order By: Relevance
“…The health‐care system encourages doctors to corrupt medical practices, ie, charging shadow payments for medical services from patients (for every visit, diagnostics, operation, etc) or earning money as agents of pharmaceutical companies on recipes and wrong recommendations. This bad practice every year worsens the quality and effectiveness of medical services, as evidenced by the lowest rating of the health‐care system in Ukraine among 32 European countries . As a result, many talented doctors and nurses leave Ukraine and find work in other countries.…”
Section: The Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The health‐care system encourages doctors to corrupt medical practices, ie, charging shadow payments for medical services from patients (for every visit, diagnostics, operation, etc) or earning money as agents of pharmaceutical companies on recipes and wrong recommendations. This bad practice every year worsens the quality and effectiveness of medical services, as evidenced by the lowest rating of the health‐care system in Ukraine among 32 European countries . As a result, many talented doctors and nurses leave Ukraine and find work in other countries.…”
Section: The Resultsmentioning
confidence: 99%
“…The recent study found that Ukraine has the most ineffective and inefficient health‐care system among 32 European countries. This country launches the health‐care reform in 2018.…”
Section: Introductionmentioning
confidence: 99%
“…A differentiation between the two concepts is rather a norm in other fields of research such as economics, management, organizational studies, strategic planning, etc. (McCormick, 1981;Bartuševičienė and Šakalytė, 2013;lo Storto and Goncharuk, 2017;Mandl, Dierx and Ilzkovitz, 2008;Codagnone, 2008), but the two concepts are often used inter-changeably in law (at least regarding the present topic, see for example Dragoș and Neamțu, 2013), with few studies addressing the differences between the two (Cornall, 2008;Ransome, 2008;Voermans, ten Napel and Passchier, 2015;European Union, 2015;OECD, 2010;Trinder and Kellett, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Since its introduction, DEA has been extensively employed in economic analysis to calculate measures of efficiencies in various situations and industries, such as transportation [29,31,32], government and public sector [33][34][35], public utilities [21,22,[36][37][38], healthcare [39][40][41], education [42,43], banking and finance [44,45], energy and environmental studies [46][47][48][49][50][51][52], manufacturing and information technology [53][54][55][56].…”
Section: Dea Methodsmentioning
confidence: 99%